2020
DOI: 10.47391/jpma.672
|View full text |Cite
|
Sign up to set email alerts
|

Design and health: an interdisciplinary baseline experience of product design for health needs of the Chilean elderly

Abstract: Abstract Objective: Describing the results of a User-Centered Design workshop using Challenge Based Learning or CBL, where students from Chilean industrial design and health degrees, developed solutions to resolve health problems among the elderly. Method: It was a pre-experimental study; 45 university students took part in a workshop: 39 from Industrial Design, 3 from Speech Therapy, 2 from Medical Technology and 1 from Medicine. In this workshop, the students, using CBL in disciplinary heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Eight studies (19%) reported using other methods, such as feedback from the judging panel and audience and votes, to evaluate the output generated during the designathon (figure 1 and online supplemental table 4). 21 25 26 31 44 46 54 58 In total, 34 studies (81%) reported having judging panels as follows: designathon participants (n=2, 5%),25 26 external expert (n=19, 45%),7 24 28–30 33–35 37 40 41 44–46 48–51 56 more than one profession (n=10, 24%)8 18 20 22 23 27 36 38 43 47 58 and others (n=6, 14%) (eg, steering committees and faculty mentors) (figure 1 and online supplemental table 4). 19 21 34 52 54 57…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (19%) reported using other methods, such as feedback from the judging panel and audience and votes, to evaluate the output generated during the designathon (figure 1 and online supplemental table 4). 21 25 26 31 44 46 54 58 In total, 34 studies (81%) reported having judging panels as follows: designathon participants (n=2, 5%),25 26 external expert (n=19, 45%),7 24 28–30 33–35 37 40 41 44–46 48–51 56 more than one profession (n=10, 24%)8 18 20 22 23 27 36 38 43 47 58 and others (n=6, 14%) (eg, steering committees and faculty mentors) (figure 1 and online supplemental table 4). 19 21 34 52 54 57…”
Section: Resultsmentioning
confidence: 99%
“…3,5,6,18,19,21,[23][24][25][26][27][28][29][30][31]33,34,[38][39][40][41][42]45,47 The median number of the final product was 8.5 (IQR 5, 13, range 2-40). The final products reported from thirty-two studies (84%) emerged as four themes: 1) educational programs (n=8, 21%), such as wellness and healthy choice programs; 16,17,23,26,27,29,44,46 2) mobile phone applications (n=7, 18%), such as management of opioids and support mental health; 20,21,28,30,31,40,41 3) medical devices (n=4, 11%), such as breast pumps and humanitarian surgical care; 3,18,25,35 and 4) mixed interventions (n=11, 29%) (Table 3). 5,6,19,24,…”
Section: Outputsmentioning
confidence: 99%
“…3,5,6,19,21,[24][25][26]28,30,31,33,36,37,39,40,42,44,49,51 Eight studies (21%) reported using other methods, such as feedback from the judge panel and audience and votes, to evaluate the product generated during the designathon (Table 3). [16][17][18]20,29,30,45,46 The judge panels included designathon participants (N=2, 5%), 29,30 external expert (N=18, 47%) 5,18,19,21,22,28,[32][33][34][36][37][38]42,43,45,[48][49][50] and more than one professions (N=11, 29%) (Table 3…”
Section: Outputsmentioning
confidence: 99%
See 1 more Smart Citation